IMPROVING STUDENTS’ LEARNING OF THE MATERIAL OF THE SHAHADA SENTENCE THROUGH THE STAD COOPERATIVE LEARNING - Jumahida; Sulaiman, Umar; Awaliah Musgamy; Syaparuddin; Aisyah Nur Syarif (Auladuna: Jurnal Pendidikan Dasar Islam, 2024)
Abstract This study explores the use of Student Teams Achievement Divisions (STAD) of the cooperative learning model to improve students' learning outcomes on the shahada sentence material in primary education. The study was conducted at SD Negeri 58 Ulo in Bone Regency using a quantitative approach using Class Action Research (CAR) and involved 15 grade 1 students. Data were collected through observation and learning outcome tests. The findings indicated that the application of the STAD cooperative learning model improved learning outcomes on the shahada sentence material. This research highlighted the importance of effective teaching methods in Islamic education at the primary school level. The results contribute to the development of more beneficial approaches in the field of primary education.